Effectiveness of mindfulness training on pregnancy stress and the hypothalamic–pituitary–adrenal axis in women in China: A multicenter randomized controlled trial - Wang, Shulei; Zhang, Chen; Sun, Mengyun; Zhang, Daming; Luo, Ying; Liang, Kairu; Xu, Tao; Pan, XiaoPing; Zheng, Ruimin; Shangguan, Fangfang; Wang, Jia (Frontiers in Psychology, 2023)
Introduction In the past two decades, mindfulness-based intervention programs have gradually become popular.Many studies have confirmed that these programs can effectively alleviate prenatal stress and negative emotion.The mindfulness-based stress-buffering hypothesis suggests that mindfulness training can induce changes in the levels of the cortisol secreted by the HPA axis, thereby reducing stress susceptibility. However, to date, only a few high-quality evidence-based medical studies have analyzed the effect of the mindfulness-based intervention in a maternal population.Thus, this study investigated the effects of a mindfulness-based psychosomatic intervention on pregnancy stress and the HYPERLINK “javascript:;” hypothalamic-pituitary-adrenal (HPA) axis of pregnant Chinese women. Methods Women experiencing first-time pregnancy (n = 117) were randomly allocated to the intervention group or parallel active control group, and data were collected at baseline and post-intervention periods. The participants completed questionnaires regarding mindfulness and pregnancy stress. Saliva samples was collected at the time of waking up, and 30, 45, and 60 min after waking up for analyzing the salivary cortisol levels. We analyzed differences between the two groups and changes within the same group before and after the intervention. Results and discussion A total of 95 participants completed the trial. Compared with the parallel active control group, the intervention group exhibited lower levels of stress after the intervention (P = 0.047). For HPA-axis-related indicators after the intervention, Delta value (P = 0.01) and AUCM value (P = 0.031) of the intervention group were significantly higher than that of the control group. Mindfulness-based interventions effectively reduced the level of pregnancy stress and adjusted the HPA axis function in pregnant women in China. Clinical Trial Registration https://www.chictr.org.cn, identifier ChiCTR 2000033149.